Spheroidization effects on the electrical and magnetic properties of Cu-Nb composites - Sandim, M.J.R.; Sandim, H.R.Z.; Stamopoulos, D.; Renzetti, R.A.; Das Virgens, M.G.; Ghivelder, L. (IEEE TRANSACTIONS ON APPLIED SUPERCONDUCTIVITY, 2006)
We report on the microstructure evolution in Cu-15% Nb multifilamentary wires upon annealing and the corresponding effects on their electrical and magnetic properties. During annealing at temperatures higher than 800 degrees C thermal instability mechanisms take place in the microstructure of the Cu-15%Nb composite, leading to spheroidization, followed by coarsening of niobium filaments. Such microstructural changes exert considerable influence on the magnitude of the normal electrical resistivity for the Cu-Nb composite. In addition, the annealing process leads to a double-peak structure in the isothermal DC magnetization curves of the composite, which is strongly dependent on the annealing time. This behavior suggests that the spheroidization kinetics can be obtained from M(H) curves.